Is John Zizioulas an Existentialist in Disguise? Response to Lucian Turcescu - Papanikolaou, Aristotle ca. 21. Jh. (Modern theology, 2004)
This essay responds to Lucian Turcescu's article, " ‘Person’ versus ‘Individual’, and Other Modern Misreadings of Gregory of Nyssa", Modern Theology Vol. 18 no. 4 (October, 2002) in which he argues that John Zizioulas's relational ontology of trinitarian personhood is indebted more to modern personalism and existentialism than to the Cappadocian Fathers. Turcescu's focus on Gregory of Nyssa does not warrant the claim that a relational ontology of personhood cannot be found within the thought of the Cappadocian Fathers. More substantively, Turcescu never addresses Zizioulas's interpretation of the Cappadocian affirmation of the monarchy of the Father, which, I argue, is central to Zizioulas's relational ontology insofar as such an ontology attempts to express the realism of divine-human communion.